The Princeton sourcebook in comparative literature from the European enlightenment to the global present - Damrosch, David 1953-; Melas, Natalie; Buthelezi, Mbongiseni 1980- (Princeton, NJ Princeton University Press, 2021)
Frontmatter -- TRANSLATION/ TRANSNATION -- CONTENTS -- INTRODUCTION -- PART ONE ORIGINS -- 1 Results of a Comparison of Different Peoples' Poetry in Ancient and Modern Times (1797) -- 2 Of the General Spirit of Modern Literature (1800) -- 3 Conversations on World Literature (1827) -- 4 From The Birth of Tragedy (1872) -- 5 Present Tasks of Comparative Literature (1877) -- 6 The Comparative Method and Literature (1886) -- 7 World Literature (1899) -- 8 From What Is Comparative Literature? (1903) -- PA R T TWO THE YEARS OF CRISIS -- 9 The Epic and the Novel (1916) -- 10 Chaos in the Literary World (1934) -- 11 From Epic and Novel (1941) -- 12 Preface to European Literature and the Latin Middle Ages (1948) -- 13 Philology and Weltliteratur (1952) -- 14 From Minima Moralia (1951) -- 15 Poetry, Society, State (1956) -- 16 Preface to La Littérature comparée (1951) -- 17 The Crisis of Comparative Literature (1959) -- PART THREE THE THEORY YEARS -- 18 The Structuralist Activity (1963) -- 19 Women's Time (1977) -- 20 Semiology and Rhetoric (1973) -- 21 Writing (1990) -- 22 The Position of Translated Literature within the Literary Polysystem (1978) -- 23 Cross-Cultural Poetics: National Literatures (1981) -- 24 The World, the Text, and the Critic (1983) -- 25 The Quest for Relevance (1986) -- PART FOUR CONTEMPORARY EXPLORATIONS -- 26 Comparative Cosmopolitanism (1992) -- 27 Literature, Nation, and Politics (1999) -- 28 Comparative Literature in China (2000) -- 29 From Translation, Community, Utopia (2000) -- 30 Crossing Borders (2003) -- 31 Evolution, World-Systems, Weltliteratur (2006) -- 32 A New Comparative Literature (2006) -- BIBLIOGRAPHIES -- CREDITS -- INDEX
Key essays on comparative literature from the eighteenth century to todayAs comparative literature reshapes itself in today's globalizing age, it is essential for students and teachers to look deeply into the discipline's history and its present possibilities. The Princeton Sourcebook in Comparative Literature is a wide-ranging anthology of classic essays and important recent statements on the mission and methods of comparative literary studies. This pioneering collection brings together thirty-two pieces, from foundational statements by Herder, Madame de Staël, and Nietzsche to work by a range of the most influential comparatists writing today, including Lawrence Venuti, Gayatri Chakravorty Spivak, and Franco Moretti. Gathered here are manifestos and counterarguments, essays in definition, and debates on method by scholars and critics from the United States, Europe, Asia, Africa, and Latin America, giving a unique overview of comparative study in the words of some of its most important practitioners. With selections extending from the beginning of comparative study through the years of intensive theoretical inquiry and on to contemporary discussions of the world's literatures, The Princeton Sourcebook in Comparative Literature helps readers navigate a rapidly evolving discipline in a dramatically changing world
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Keywords: LITERARY CRITICISM / Reference; Literature; Poetry; Comparative Literature; Writing; Criticism; World Literature; Romanticism; Prose; Philosophy; Theory; Literary Criticism; Philology; Genre; Writer; Novelist; Ideology; The Other Hand; Narrative; Modernity; Thought; Essay; Linguistics; Grammar; Roland Barthes; Philosopher; Superiority (short story); Classicism; Jacques Derrida; Western Culture; Rhetoric; Akivaga, Samora; Aristophanes; Aristotle; Augustine of Hippo; Bach, Johann Sebastian; Beckett, Samuel; Benjamin, Walter; Bin Xin; Blackburn, Dougal; Candido, Antonio; Carter, Martin; Cervantes, Miguel de; Coleridge, Samuel Taylor; Conrad, Joseph; Curtius, Ernst Robert; Dante Alighieri; De Quincey, Thomas; Dostoyevsky, Fyodor; Dumézil, Georges; Eliot, Thomas Stearns; Eschenburg, Johann Joachim; Featherston, Mike; Futabatei, Shimei; Fénelon, François; Gervinus, Georg Gottfried; Habermas, Jürgen; Hawthorne, Nathaniel; Hemingway, Ernest; Hofmannsthal, Hugo von